Plan to Turn Your Company Around in 90 Days HOW TO RESTORE POSITIVE CASH FLOW AND PROFITABILITY - Lack, Jonathan H. (Apress : Imprint: Apress, 2013)
More than half of all businesses in the U.S. dont make it to their fifth birthday, and nearly 70 percent are gone by year ten. How do businesses get into trouble? A hundred different ways. Poor cash flow, undercapitalization, lax financial controls, poor worker productivity, boneheaded mistakes, inefficient processes, failure to adapt, loss of enthusiasm . . . the list goes on and on. The fact is, many businesses that face life-threatening challenges, or are just stuck in the doldrums,can turn their fortunes around. And Jonathan Lack is the expert who can show you how. Lack is a turnaround specialistthe guy called in to reinvigorate a stalled company or revamp the poor practices that reduce sales and decimate profits. Once hes done, the company is again on the road to growth and profitability. Plan to Turn Your Company Around in 90 Days is a pragmatic, step-by-step guide to helping your company not only survive but begin to grow again.Among other things, this book will teach you how to improve your companys cash flow, how to better manage your payroll and employee productivity, and how to get better results from your marketing and sales efforts. Turn Your Company Around in 90 Days will help you develop a framework to create a strategic plan that will move your company in the right direction and breathe new life into tired or worn-out operations and products. Plan to Turn Your Company Around in 90 Days will immediately help your firm in the following areas: How to get to cash flow positive and then grow How to manage technology better How to manage your payroll and employee productivity How to improve marketing and increase sales How to restore profitability How to manage your board of directors and investors If youre at all fearful that your company may not last the next couple of years, this book is for you.